Management of Development that Affects the Quality of Life of People with Disabilities by the Department of Promotion and Improve the Quality of Life of the Disabled in the Central Region - Siwilai, Thapthim; Khanthahat, Phamorn; Yeunyong, Tanisorn (Rajapark Journal, 2022)
The objectives of this research were 1) to study the quality of life of people with disabilities 2) to study factors affecting the quality of life of people with disabilities 3) to propose guidelines for developing the quality of life of people with disabilities by the Department of Empowerment of Persons with Disabilities in the central region as quantitative and qualitative research the target population was 400 people with mobility or physical disabilities in the central region. The research tools were questionnaires and in-depth interviews. The statistics used were frequency, percentage, mean, standard deviation, multiple regression, and analysis. Content the study found that 1) The quality of life of people with disabilities by the Department of Empowerment of Persons with Disabilities in the central region as a whole, at a high level when considering each aspect, it was found that physical, social, mental and environmental aspects. Were at a high level, respectively 2) Occupation and promotion and protection of rights affecting the quality of life of people with disabilities statistically significant at the .05 level 3) Should encourage persons with disabilities to access benefits, rights, and protection to improve the quality of life of the disabled.